Global, regional, and national disease burden of tobacco-related Alzheimer’s disease among individuals over the age of 55: a global burden of disease study - Dong, Tianyi; Zhang, Shipeng; Wang, Hanyu; Jiang, Yanjie; Zhang, Qinxiu; Li, Xueying; He, Lanfang (Frontiers in Public Health, 2025)
BackgroundAlzheimer’s disease is a progressive neurodegenerative disorder characterized by an insidious onset. Numerous studies have identified a significant association between tobacco use and Alzheimer’s disease. This study aims to explore the epidemiological patterns and trends concerning tobacco-related Alzheimer’s disease at global, national and regional levels.MethodsWe analyzed data on mortality, age-standardized DALY rate (ASDR), and estimated annual percentage changes (EAPCs) sourced from the Global Burden of Disease data for 2021. The analysis was further stratified by country and region, socio-demographic index (SDI), gender, and age. A Bayesian Age-Period-Cohort (BAPC) model was employed to project the global burden in the future.ResultsIn 2021, the total burden revealed a decline in the number of deaths and ASDR compared to 1990. The highest proportions of mortality and ASDR were observed in the age group over 95 years. The disease burden among men was significantly higher than of among women, approximately three times greater. Conversely, in Australia and North America, the burden of disease among women surpassed that of men. In most of the 21 regions worldwide, both mortality and ASDRs have decreased since 1990, and intra-regional mortality rates have declined as SDI has increased. It is anticipated that the burden will continue to gradually decrease from 2021 to 2040.ConclusionAlthough the global burden of tobacco-related Alzheimer’s disease among the older adults declined from 1990 to 2021, significant disparities existed across regions, age groups, sex, and SDI.